THE IMPORTANCE TO UNDERSTAND THE AL-QUR’AN AND KNOWLEDGE (PENTINGNYA MEMAHAMI AL-QUR’AN DAN ILMU PENGETAHUAN) - Zaedi, Muhamad (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
The article is aims to explore the importanc to understand the Al-Qur’an and knowlegde. Al-Qur’an is a source of knowledge. This jurnal is made to know the relation between Islam and knowledge, The relation between Al-Qur’an and science, the relation between Al-Qur’an and math, to knowing the expansion between knowledge and Al-Qur’an and, to knowing knowledge and technology. The law of seking knowledge is fardhu ‘ain. (the personal have to do). According to the monitoring, al-qur’an contains all of information that human need. Al-quran as asource of knowledge gives the seeds of knowledge to be expanded by human become a science and technology that very useless. Science correspondency with the nature accident, so in al-quran more than 750 ayat about the nature accident. So the conclusion is , Al-Quran and knowledge are the one of unity that can’t be separate. Artikel ini bertujuan untuk menelusuri pentingnya memahami Al-Qur’an dan ilmu pengetahuan. Al-Qur'an adalah sumber pengetahuan. Jurnal ini dibuat untuk mengetahui hubungan antara Islam dan pengetahuan, Hubungan antara Al-Qur'an dan sains, hubungan antara Al-Qur'an dan matematika, untuk mengetahui ekspansi antara pengetahuan dan Al-Qur'an dan, untuk pengetahuan dan teknologi. Hukum pengetahuan seking adalah fardhu ‘ain. (yang harus dilakukan pribadi). Menurut pemantauan, al-qur’an berisi semua informasi yang dibutuhkan manusia. Al-quran sebagai sumber pengetahuan memberi benih-benih pengetahuan untuk dikembangkan oleh manusia menjadi ilmu dan teknologi yang sangat tidak berguna. Ilmu korespondensi dengan kecelakaan alam, sehingga dalam al-quran lebih dari 750 ayat tentang kecelakaan alam. Jadi kesimpulannya adalah, Al-Quran dan pengetahuan adalah satu kesatuan yang tidak dapat dipisahkan.